Relationship of location, infrastructure, and transportation of Productive Malaysia Cocoa Farmers (PMCF) towards work performance in Sarawak, Malaysia - Arif Shah, Jasmin; Sulaiman, Winoryantie; Mohamed Haris, Nur Bahiah; Kasin, Ramle (HH PUBLISHER, 2024)
Malaysian cocoa production has relied on cocoa farmers since 2006 because they were the primary holders (81.4%) of the cocoa cultivation area. As for Sarawak, 100% of cocoa production was from cocoa farmers. Sarawak used to produce 21,200 metric tons of dried cocoa beans in 1990. The government also has spent more on training and fertilizer for cocoa farmers to increase PMCF productivity. However, the production keeps gradually decreasing yearly. In 2021, Sarawak only produced 59 metric tons of dried cocoa beans, and the productivity decreased by 10% to 0.19 metric/ton/ha/year compared to 2019 productivity. Driven by the Iceberg Model, the objectives of this preliminary study are to determine i) the location, infrastructure and transportation towards work performance levels, ii) the relationship between location, infrastructure and transportation with work performances, iii) the most important factors (IVs) that influence more toward work performances. A total of 35 respondents were involved in this purposive data collection, which is only 30% of the sample population of the preliminary study, which was 105 PMCF. The sampling strategy employed a random sample technique. These 35 respondents were selected, involving 3.6% of respondents for each zone population of Sarawak rural areas, namely the Northern, Middle, and Southern Coastal Zone. The data was processed using IBM SPSS version 25.0. The data were tested by employing Exploratory Factor Analysis (EFA), and subsequent analysis was performed utilizing descriptive, correlation, and regression techniques to address the study's objectives. The study found that all the variables showed moderate-level indicators. The variables that showed moderate and positive correlation were location and infrastructure. In contrast, location is the most significant contributing factor to PMCF's work performance in Sarawak.